The parental error and applied parental control - Szymańska, Agnieszka (Studia Psychologica: Theoria et praxis, 2011)
There was explored the connection among parental directiveness, child behaviour and parental difficulty. We put forward a hypothesis that parents of “difficult” children would achieve higher scores in aggressive directiveness, parents of well-behaved children would achieve higher scores in heart - full directiveness. It was expected that parental difficulty would determinate upbringing mistake. The sample consisted of 204 people, parents of children who attend to kindergartens in Warsaw, Cracow, Częstochowa. Results confirmed research hypotheses: parents of “difficult” children achieved higher scores in aggressive directiveness, parents of well-behaved children achieved higher scores in heart - full directiveness. A spectacular outcomes demonstrate the crucial role of the type of parental directiveness, and prove that parental difficulty determinates parental mistake but only in group of “difficult” childrens parents.